Analyzing Sociocultural Identities through Creative Writing with Fifth Graders at San Isidro school in Pauna, Boyacá (2018)
This research study was developed at San Isidro School, which is a public institution located in the rural area of Pauna, Boyacá. The school is located in the countryside and it is about 30 minutes by car and 60 minutes on foot. That school is focused on the agronomy and farm activities, which means that students learn different aspects about the caring of environment, especially plants and animals in order to keep working for the improvement of the farm. The school is small due to the quantity of students that currently are studying there. The school offers several facilities such as a little park where students and teachers can rest and interact during the break, a restaurant where students can have their lunch, bathrooms for girls and boys, a computer room with 10 computers, a television and a stereo system. They don´t have access to internet but they try to use these tools once or twice a week not only in their systems classes, also in others like Spanish, English and math classes. The selected population for that research is fifth grade at San Isidro school, there are 12 students 8 girls and 4 boys. Their ages range are from 9 to12 years old. Their lives conditions are not easy due to some of them are forced to work before and after school. This situation limits students to arrive home and do their homework or tasks because of lack of time, support, materials or resources. In their schedule, they have two classes of English a week and this is other factor to take into account in the language learning process, because timing is very short for the development of a better English level. Besides, English guidelines and syllabus are based on basic vocabulary such as numbers, places, professions, among others, but students do not have a deep explanation in terms of grammar and oral production. Additionally, there is only one teacher for the whole areas, she has to teach all the subjects. Observing the routines of students, it is possible determine that living in the rural area has lots of disadvantages for students’ learning because their parent’s economy is not the best due to the lack of opportunities to work. Despite the distance and the life conditions of students, they are very positive, talented, dynamic, creative and clever. Also, they feel motivated and encouraged to improve themselves because they show interest in carrying out a good life project.